PROBLEMS OF ORGANIZATION OF CONTINUOUS PROFESSIONAL DEVELOPMENT OF SECONDARY SCHOOL TEACHERS - Fayzieva Makhbuba (Researchparks Publishing, 2022)
The current situation in the continuous professional development of teachers, what technologies they use to study the educational, pedagogical, technological, organizational, economic, socio-cultural factors, how long they can study independently, the level of use of technology and through what methods information on the results of the study of problems, such as improving their skills.